Arzneitherapie des älteren Menschen - Wehling, Martin (Zeitschrift für Gerontologie und Geriatrie, 2017)
Elderly people are the most rapidly growing sector of our society. Due to their multimorbidity they are exposed to a multitude of medications, which are accompanied by chances and risks. The problem of inappropriate medication in the elderly is exacerbated by the fact that only a holistic view can help these patients and that this is predominantly the responsibility of the general practitioner. The closely measured paid contact time is often insufficient to optimize complex medications. Clinically successfully tested aids in the form of lists give reason for hope: in particular, the positive/negative assessment of limitations of the elderly with respect to drugs by the STOPP/START criteria and the FORTA classification are clinically successful aids. Purely negative lists, such as the Beers or PRISCUS lists, have been disappointing in clinical application because they do not consider the needs, prognostic and particularly symptomatic importance and weighting of the diagnosis of patients. Further implementation of these aids to decision making should help to improve the problem of care of elderly patients in the field of drug treatment, even in IT systems.
Gesehen am 04.04.2019